Phytochemical, Pharmacological Profile and Biotechnology Approaches in the Production of Coriandrum sativum Linn. - Singh, Sonia; Sharma, Khushi; Goswami, Manisha; Sharma, Himanshu (Current Organic Chemistry, 2023)
The plant coriander, family umbelliferae, has applications in both the culinary and traditional medical fields. It has a wide variety of phytochemicals, including polyphenols, vitamins, and many phytosterols. These phytoconstituents are responsible for the pharmacological activities of coriander, which include anticancer, anti-inflammatory, anti-diabetic, and analgesic actions. The following online resources were utilised to conduct an electronic search of the available literature: PubMed, Scopus, Google Scholar and ScienceDirect. Studies in traditional breeding techniques resulted in the production of new species over time. In this light, it is of the utmost need to carry out fundamental research on contemporary breeding programmes to ascertain coriander's quantity and quality performance. Through the use of genome sequencing technology and various molecular markers, researchers were able to examine the genetic diversity and population structure of the coriander plant. As a result of these studies, coriander breeding made some significant strides forward. The objective of this manuscript is to provide attention on the significant role that advances in biotechnology play in the breeding of coriander and to further evaluate and discuss the effectiveness of C. sativum in the treatment of several diseases. In addition to this, the manuscript includes a discussion of the phytoconstituents that may be found in coriander seed and that have been collected from all over the world. In light of this information, the application of biotechnological methods has the potential to improve coriander breeding.
Keywords: Breeders